BdorOR88a Modulates the Responsiveness to Methyl Eugenol in Mature Males of Bactrocera dorsalis (Hendel) - Liu, Huan; Chen, Zheng-Shi; Zhang, Dong-Ju; Lu, Yong-Yue (Frontiers in Physiology, 2018)
Insect attractants are important prevention tools for managing populations of the Oriental fruit fly, Bactrocera dorsalis (Hendel), which is a highly destructive fruit-eating pest causing substantial economic damage to the fresh produce industry worldwide. Methyl eugenol (ME) is still considered the gold standard of B. dorsalis attractants. Mature male flies use their sense of smell to detect ME, but the molecular mechanism underlying their olfactory detection of ME largely remains unclear. Here, we showed that ME activates the odorant receptors OR63a-1 and OR88a in mature B. dorsalis males. Interestingly, ME only elicited robust responses in the BdorOR88a/BdorOrco-expressing Xenopus oocytes, thus suggesting that BdorOR88a is necessary for ME reception and tropism in B. dorsalis. Next, our indoor behavioral assays demonstrated that BdorOR63a-1 knockdown had no significant effects on ME detection and tropism. By contrast, reducing the BdorOR88a transcript levels led to a significant decrease in the males’ responsiveness to ME. Taken together, our results fill a key gap in the understanding of the olfactory background to the Oriental fruit fly’s attraction towards ME.